Implementasi Kebijakan Pengangkatan Perangkat Desa Di Wilayah Kabupaten Sukabumi (Studi Atas Desa Jagamukti) - Muhammad Fatwa Fadhila; Dine Meigawati; Andi Mulyadi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This study analyzes the implementation of the village apparatus appointment policy in Jagamukti Village, Surade District, Sukabumi Regency, based on Sukabumi Regent Regulation Number 34 of 2021. It is motivated by indications of discrepancies between regulations and actual practices, such as alleged direct appointments without proper selection stages. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation involving the Village Head, District Secretary, and Analyst Staff of the Sukabumi Regency Community and Village Empowerment Office. Data were analyzed using the Mazmanian and Sabatier implementation framework. The results indicate that formally, the appointment procedures comply with applicable regulations. However, policy effectiveness is hindered by limited human resource quality, high demands for information technology mastery, strong subjectivity factors, and social environmental pressures from the community. Therefore, this study recommends implementing a stricter merit-based selection system, enhancing village apparatus capacity, and conducting more proactive bureaucratic supervision to achieve policy objectives optimally.